Current Status of Family Poultry Production in Togo - Talaki, E.; Dzogbema, K.F.X.; Adjrah, Y.; Tona, K. (International Journal of Poultry Science, 2020)
Background and Objective: Appropriate poultry development strategies based on sound knowledge of family poultry practices can benefit households substantially by contributing to food security, women’s empowerment and poverty reduction in developing countries. This study was conducted to obtain information on family poultry practices in Togo. Materials and Methods: This baseline study on family poultry production was carried out in the five regions of Togo. Semi-structured questionnaires were used by trained investigators to collect data through individual interviews in 1,468 households. Results: The results showed that the majority of men in Togo (65.48%) owned poultry and that agriculture is the predominant occupational activity of most (91.35%) poultry farmers. The leading purposes for keeping poultry species were for personal food consumption and income (39.37%). Birds were most often (87.10%) purchased to form the initial poultry flock. Body size was reported by 21.67% of respondents as the trait that most influenced the choice of purchase, followed by a combination of body size and plumage (23.16%). The poultry owned were mainly chickens (n = 50±7), followed by pigeons (n = 31±7) and Guinea fowl (n = 23±5). Cereals were the major feed constituents, particularly maize (95.09%), followed by millet (43.71%), leftovers (35.32%) and sorghum (34.49%). The main sources of water supply for poultry maintenance were wells (36.07%) and boreholes (32.97%). Disease (66.16%), theft (20.17%) and predation (11.54%) were the leading causes of poultry loss. The most common of these diseases were Newcastle disease, coccidiosis, smallpox, bronchitis, salmonellosis, vitamin deficiency and intestinal worms. Approximately 33.15% of respondents reported having provided veterinary care, whereas herbal treatments were used by 46.62% of respondents to prevent or treat diseases in poultry flocks. More than half (55.24%) of the respondents had access to extension services support and 81.38% reported being satisfied with the support provided. Conclusion: Poultry diseases, lack of information and training on management practices are the important constraints in the current status of family poultry production in Togo. The findings obtained from this study are important in determining the resources needed to improve family poultry farming in Togo.